Three performative (re) inscriptions: to dislocate pedagogy, to expand teaching and to stop social pain (Praxis Educativa, 2019)
In Argentina during 2018 in different universities, institutes and schools sharp interruptions came up in defense of the public education –secular and free of charge. In this text, three performative (re)inscriptions are derived, inquiring into categories,or narratives as we prefer to call them, which we share in the scientific production of our academic community–Research Group on Cultural Studies of the National University of Mar del Plata-. Thus, based on our own interruptions and with our publicly legitimated institutional capacity to produce knowledge in the field of education sciences, we state three performative (re)inscriptions: to dislocate pedagogy, to expand teaching and to stop social pain. To do so, we recover the urge for an epistemological eviction of our (self)arrogance and we restore a first person as a condition of a friendlier coexistence.
Keywords: science; social pain; narrative research; pedagogy.